Standards of analgesic treatment versus hospital practice - Lewandowska, Anna; Misiąg, Anna; Lewandowski, Tomasz; Laskowska, Barbara (Journal of Education, Health and Sport, 2017)
Introduction: Pain remedying is a fundamental patient law. Modern medicine is acknowledging the mechanism and the warp of pain, commanding more efficient therapeutic means allowing to control the pain. Multidirectional pain therapy uses variable techniques and medicines which enables to maximize the analgesic effect during the reduction of side effects of each method. Objective: Evaluation of applying standards of analgesic treatment in hospital practice. Material and methods: There were 100 people with severe pain who underwent surgical and orthopedic treatment, as well as, the ones with chronic pain, staying in neurological ward who took part in the examination. Choice of examined patients was random and embraced hospitals patients in the Podkarpackie voivodeship with “Szpital bez Bólu” (eng.: Hospital without pain) certificate. Examined group comprised of : 57% of women and 44% of men, living in rural (56%) and urban (44%) area. Research methods used in the examinations, were diagnostic opinion poll, records analysis and pain measurements. Results: 42 % of patients can feel the pain intermittently, 37% is not able to estimate how often do pain ailments occur, however, 21% of people suffer from chronic pain ailments. Patients have estimated their pain as follows: severe (26%), difficult to determine (20%), shooting (16%), burning (15%), radiating (10%), dull (8%), stinging (3%) and the one which appears when touched (2%). Having estimated the pain intensity, 53% of respondents claimed that they feel medium pain intensity and 33% claimed to have felt great pain. Nurses in the post-op (54%) and anesthesiologist (26%) are the one, to inform patient about possibilities and eventual methods of post-operative pain management. Conclusions: Pain limits physical functioning of patient. Five-stage scales included in the examination, were VAS and VRS which are sufficient in prophylaxis and pain alleviation but not entirely readable and understandable for all patients. Education of patient influences on the awareness and abilities of evaluating the pain.